Ultrasonic Elastography in the Differential Diagnosis of Thyroid Nodular Patholog - L. A. Timofeeva; M. G. Tukhbatullin; A. N. Sencha (Кубанский научный медицинский вестник, 2019)
Aim. In this study, we set out to determine the informative value of multi-parametric ultrasound examination using ultrasound elastography in the differential diagnosis of thyroid nodular neoplasms.Materials and methods. We analysed 229 multi-parametric ultrasound examinations of patients in the preoperative period in order to assess the effectiveness of strain elastography (SE) and shear wave elastography (SWE) drawing on the example of ARFI and Strain Ratio. Two patient groups were formed. The fi rst group (N1=93) included patients with thyroid cancer, whereas the second one (N2=136) was composed of patients with benign thyroid nodules (thyroid adenoma and follicular or colloid goitre). The control group consisted of 174 patients with unchanged thyroid parenchyma. SE visualised tissue elasticity as a colour map. Shear wave elastography (SWE) — ARFI and Strain Ratio techniques — was performed using the following ultrasonic apparatuses: Acuson S-2000 (Siemens, Germany), Ultrasonix SP (Sonix, Canada) and Mindray DC-8 (Mindray, China).Results. According to the obtained data (SE technique), the parenchyma of the unchanged thyroid gland exhibited heterogeneous, uneven fi ne / moderately granular, symmetrical staining (96.6%). Thyroid cancer was characterised by a shear wave velocity (ARFI) of greater than 3.57 m/s, as well as a density ratio (elasticity modulus and Strain Ratio) of more than 1.56.Conclusion. The study revealed that the application of ultrasound elastography is highly informative in the comprehensive diagnosis of thyroid nodular neoplasms and should be used when thyroid cancer is suspected to ascertain the size of nodules, as well as the tumour invasion into surrounding tissues.